Tinjauan atas Perubahan Batas Waktu Pelaporan Pajak Daerah: Studi pada Badan Pendapatan Daerah Kabupaten Bojonegoro - Hirrya Pradiptarani; Lisa Kartikasari; Sri Dewi Wahyundaru; Sutapa Sutapa (Universitas Islam Sultan Agung, Faculty of Economic and Business, Accounting Dept, 2025)
AbstractThis study examines the implementation of changes to local tax reporting deadlines in Bojonegoro Regency, from 30 days to 15 days under the Law on Financial Relations between the Central Government and Regional Governments (UU HKPD) and the Government Regulation on General Provisions of Regional Tax and Retribution (PP KUPDRD), focusing on problems of deadline calculation and its impact on taxpayer compliance. The objectives are to analyze local government adaptation, assess policy impacts, and explore strategies of Bojonegoro’s revenue agency. Using qualitative case study methods and in-depth interviews with tax officials, data were analyzed through institutional theory. Key findings include: (1) regulatory adaptation via Regional Regulation No. 5/2023 and SIMPADU digital integration; and (2) dual impacts of improved digital efficiency versus increased administrative burdens for SMEs This study contributes in enriching local tax policy literature through institutional theory.Keywords: Regional Tax, Deadline, Institutional Theory, Bojonegoro. AbstrakPenelitian ini mengkaji implementasi perubahan batas waktu pelaporan pajak daerah di Kabupaten Bojonegoro dari 30 hari kalender menjadi 15 hari kerja pasca berlakunya UU HKPD dan PP KUPDRD, dengan fokus pada masalah perhitungan tenggat waktu dan dampaknya terhadap kepatuhan wajib pajak. Tujuan penelitian adalah menganalisis adaptasi pemerintah daerah, menilai dampak perubahan, serta mengeksplorasi strategi Bapenda Bojonegoro. Metode kualitatif dengan pendekatan studi kasus dan wawancara mendalam dengan fiskus digunakan, dianalisis melalui lensa teori institusional. Temuan menunjukkan: (1) adaptasi regulatif melalui Perda No. 5/2023 dan integrasi sistem SIMPADU; dan (2) dampak dualistik berupa peningkatan efisiensi digital di satu sisi dan beban administratif UMKM di sisi lain. Penelitian ini berperan dalam pengayaan literatur kebijakan pajak daerah berbasis teori institusional.Kata Kunci: Pajak Daerah, Tenggat Waktu, Teori Kelembagaan, Bojonegoro.